Electroporation of the Liver: More Than 2 Concurrently Active, Curved Electrodes Allow New Concepts for Irreversible Electroporation and Electrochemotherapy. (8th November 2018) - Ritter, Andreas; Bruners, Philipp; Isfort, Peter; Barabasch, Alexandra; Pfeffer, Joachim; Schmitz, Jula; Pedersoli, Federico; Baumann, Martin
Irreversible electroporation and electrochemotherapy are 2 innovative electroporation-based minimally invasive therapies for the treatment of cancer. Combining nonthermal effects of irreversible electroporation with local application of chemotherapy, electrochemotherapy is an established treatment modality for skin malignancies. Since the application of electrochemotherapy in solid organs is a promising approach, this article describes a novel electrode configuration and field generating method. For the treatment of hepatic malignancies, the shape of the electric field should resemble a spherical 3-dimensional geometry around the target tissue inside the liver. To adapt the actual shape of the field, the probe is designed in computer-aided design with a live link to a computer simulation software: Changes in design can be revalued quickly, regarding different quality criteria for field strength inside and outside the tumor. To rate these criteria, a set of formulas with weighting coefficients has been included. As a result of this design process, a needle-shaped prototype applicator has been built, designed for an intracorporal electroporation-based treatment. It can be used as percutaneous, image-guided, minimally invasive treatment option for malignant liver tumors. The shaft of the probe is used as central electrode and fitted with additional 4 expandable electrodes. These satellite electrodes are hollow, thus serving as injectors for chemotherapeutic agents within the area of the electric field. This configuration can be used for electrochemotherapy as well as irreversible electroporation. By placing 5 electrodes with just one needle, the procedure duration as well as the radiation dose can be reduced tremendously. Additionally, the probe offers an option to adapt the field geometry to the tumor geometry by connecting the 5 electrodes to 5 individually chosen electric potentials: By fine-tuning the ablation zone via the potentials instead of adjusting the location of the electrode(s), the procedure duration as well as the radiation dose will decrease further.